Implementasi Penggunaan Platform Digital dalam Pembelajaran Bahasa Arab - Huda, Ahmad Nawirul; Fadzilah, Nurul; Zen, Aatina Khairal Athiyyah; Mustofa, Syaiful (Prosiding Konferensi Nasional Bahasa Arab, 2023)
Digital platform’s development can improve students' abilities and quality in learning Arabic. This research aims to reveal Arabic language learning through digital platforms. This study uses a qualitative approach with descriptive methods. Data collection was carried out through primary data sources, namely master students in Arabic language education at UIN Maulana Malik Ibrahim Malang, class B, the first semester of 2023, and secondary data sources included documents in the form of journals, websites and applications. Data collection techniques use documents and interviews. Data analysis is in the form of data reduction, data classification, data analysis, and conclusions. The results of this research show that learning Arabic through digital platforms includes three factors, namely learning media, social media, and digital dictionaries. Learning media include Duolingo, Kahoot, and Quizziz. Social media includes Instagram, WhatsApp and TikTok. As well as digital dictionaries including Google Translate, Bing Translator, and Ma'ani Dictionary.